Disease Burden Estimates of Respiratory Syncytial Virus related Acute Respiratory Infections in Adults With Comorbidity: A Systematic Review and Meta-Analysis - Shi, Ting; Vennard, Sophie; Jasiewicz, Francis; Brogden, Rory; Nair, Harish (The Journal of infectious diseases, 2022)
Respiratory syncytial virus related acute respiratory infection (RSV-ARI) constitutes a substantial disease burden in adults with comorbidities. We aimed to identify all studies investigating the disease burden of RSV-ARI in this group.BACKGROUNDRespiratory syncytial virus related acute respiratory infection (RSV-ARI) constitutes a substantial disease burden in adults with comorbidities. We aimed to identify all studies investigating the disease burden of RSV-ARI in this group.We estimated the incidence, hospitalization rate, and in-hospital case fatality ratio (hCFR) of RSV-ARI in adults with comorbidities based on a systematic review of studies published between January 1996 and March 2020. We also investigated the association between RSV-ARI and any comorbidity in adults. Meta-analyses based on random effects model were carried out.METHODSWe estimated the incidence, hospitalization rate, and in-hospital case fatality ratio (hCFR) of RSV-ARI in adults with comorbidities based on a systematic review of studies published between January 1996 and March 2020. We also investigated the association between RSV-ARI and any comorbidity in adults. Meta-analyses based on random effects model were carried out.Overall, 20 studies were included. The annual incidence rate of RSV-ARI in adults with any comorbidity was 37.6 (95% confidence interval [CI], 20.1-70.3) per 1000 persons per year in industrialized countries and the seasonal incidence rate was 28.4 (11.4-70.9) per 1000 persons per season. The hCFR in industrialized countries was 11.7% (5.8%-23.4%). There were no studies in developing countries. There were insufficient data to generate the meta-estimate of hospitalization rate. The likelihood of experiencing RSV-ARI for those with any comorbidity compared to those without was estimated to be 4.1 (odds ratio [OR], 1.6-10.4) and 1.1 (OR, 0.6-1.8) from studies using univariable and multivariable analysis respectively.RESULTSOverall, 20 studies were included. The annual incidence rate of RSV-ARI in adults with any comorbidity was 37.6 (95% confidence interval [CI], 20.1-70.3) per 1000 persons per year in industrialized countries and the seasonal incidence rate was 28.4 (11.4-70.9) per 1000 persons per season. The hCFR in industrialized countries was 11.7% (5.8%-23.4%). There were no studies in developing countries. There were insufficient data to generate the meta-estimate of hospitalization rate. The likelihood of experiencing RSV-ARI for those with any comorbidity compared to those without was estimated to be 4.1 (odds ratio [OR], 1.6-10.4) and 1.1 (OR, 0.6-1.8) from studies using univariable and multivariable analysis respectively.The disease burden of RSV-ARI among adults with comorbidity is substantial with limited data available.CONCLUSIONThe disease burden of RSV-ARI among adults with comorbidity is substantial with limited data available.